Special paperAtopic dermatitis: current treatment guidelines. Statement of the experts of the Dermatological Section, Polish Society of Allergology, and the Allergology Section, Polish Society of Dermatology - Nowicki, Roman; Trzeciak, Magdalena; Wilkowska, Aleksandra; Sokołowska-Wojdyło, Małgorzata; Ługowska-Umer, Hanna; Barańska-Rybak, Wioletta; Kaczmarski, Maciej; Kowalewski, Cezary; Kruszewski, Jerzy; Maj, Joanna; Silny, Wojciech; Śpiewak, Radosław; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Atopic dermatitis (AD) is a condition frequently encountered in medical practices across the country. More than 60% of children with AD are at risk to develop allergic rhinitis or asthma (the atopic march). Patients with AD have a unique predisposition to colonization or infection by Staphylococcus aureus. Treatments for AD need to rapidly control symptoms of the disease, improve quality of life and prevent exacerbations. Given the chronic and relapsing nature of the disease, therapies need to encourage good compliance and be well tolerated.